Nature And National Identity After Communism: Globalism The Etnoscape - Katrina Z.S.Schwartz (University Of Pittsburgh Press, 2006)
In this groundbreaking book, Katrina Schwartz examines the intersection of enviromental politics,globalization,and national identity in a small east european country